Coloured reference markers in image-guided surgery - Elsamnah, Fahed S. A. (Kulliyyah of Engineering, Internatioal Islamic University Malaysia, 2015)
Image-guided Surgery is an advanced medical navigation technology that enhances surgical operations and outcomes. It plays a significant role in surgical operations, since it provides a reliable localization and tracking of human body parts. The possibility of three-dimensional visualization of the patient's body is the fundamental contribution of image-guided surgery system in medical surgery. This research attempts to implement coloured markers as an alternative to infrared markers in image-guided surgery. Three coloured markers have been used as references of visualizing a patient's body part by providing many advantages, such as an unbounded objects tracking, an inexpensive system compared to the Infrared markers system, and an unrestricted working area. The line of sight between the camera and the markers causes an interruption of the tracking system if it lost during the operation. This research introduces a multi-stereo camera system to overcome the line of sight problem, and to improve the accuracy of the image-guided surgery system. A pair of stereo cameras has been applied to recognize and detect the reference markers and visualize a patient's body part and a surgical needle. The results showed that using a coloured marker as a reference with stereo vision, a good accuracy of visualization 2.53 mm root mean square error performance at the distance of 770 to 970 mm was generated. The root mean square error of the angles Alpha (α), Theta (θ) and Phi (φ) was 1.32 degree. The execution time period of the system was about 0.35 second (3 frames per second) for multi-stereo vision, while it was 0.11 sec for stereo cameras (9 frames per second). Image filtering techniques have been used to process the captured images. The medical instrument has been visualized on Solidworks Animator and directing it from Matlab via Cadlab toolbox in real-time. Eventually, image-guided surgery system based on coloured markers and multi-stereo camera contributes promising results of medical navigation and enhances the capabilities of image-guided surgery system.